SRT3025-loaded cell membrane hybrid liposomes (3025@ML) enhanced anti-tumor activity of Oxaliplatin via inhibiting pyruvate kinase M2 and fatty acid synthase - Xiaobin Wang; Shulin Li; Zichen Li; Zhuona Lin; Zhifeng Wang (Lipids in Health and Disease)
Abstract Background Bladder cancer is one of the most common malignancies of the urinary system. Despite significant advances in diagnosis and treatment, the compromised therapeutic effect of chemotherapeutic agents, such as Oxaliplatin (OXA), remains a major clinical challenge. Thus, a combination therapy is required to enhance the OXA’s therapeutic effectiveness and improve patient outcomes. Methods The thin film hydration method was used to prepare the liposomes. Drug encapsulation efficiency and loading capacity were determined to investigate the advantages of the SRT3025-loaded cell membrane hybrid liposomes (3025@ML). Bladder cancer cell lines T24 and 5637 were cultured in McCoy’s 5 A and RPMI 1640 medium, respectively. The Cell Counting Kit-8 assay was used to determine the cell viability by treating cells with a medium containing either the vehicle solution (control), the cell membrane hybrid liposomes (ML), 3025@ML, or compound 3 K. The antiproliferative activities were investigated after treating cells with OXA + 3025@ML and compound 3 K + OXA. Cell death and apoptosis were quantified by trypan blue and Annexin V-APC/PI apoptosis assay after treating cells with control, OXA, OXA + 3025@ML, and 3025@ML. Western blot analysis was performed after treating cells with 3025@ML, OXA, 3 K, 3025@ML + OXA, and 3 K + OXA to determine the protein levels of pyruvate kinase M2 (PKM2) and fatty acid synthase (FASN), etc. Results The present study demonstrated that 3025@ML enhances the chemotherapeutic effect of OXA. 3025@ML + OXA treated T24 and 5637 cells showed that combination therapy significantly reduced cell viability and increased cell death rate. Flow cytometry analysis showed that the combination of 3025@ML and OXA significantly increased the percentage of apoptotic cells in T24 cells. 3025@ML and compound 3 K reduced the levels of FASN in T24 and 5637 cells and increased the anti-tumor activity of OXA. Mechanistic studies showed that 3025@ML inhibited the PI3K/AKT/mTOR signaling pathway and reduced the expression of key metabolic regulators PKM2 and FASN. Furthermore, this study demonstrated that targeting lipid metabolism and inhibiting FASN can effectively overcome the compromised therapeutic effect of OXA. Conclusion The study demonstrated that 3025@ML significantly enhances the anti-tumor activity of OXA. This novel drug delivery system inhibits key metabolic pathways, which increase DNA damage and tumor cell apoptosis. The results indicate that 3025@ML is a promising therapeutic strategy for overcoming OXA’s compromised therapeutic effect and potentially improving cancer treatment outcomes.